INDUSTRIAL EVALUATION OF RE-DRY STRATEGY FOR SOFTWOOD LUMBER - Diego Elustondo (Maderas: Ciencia y Tecnología, 2005)
This paper presents an experimental evaluation of the first commercial scale dry-sort-redry (DSRD) strategy for drying of 2x4 Pacific coast hemlock (PCH) lumber. The DSRD strategy is a methodology designed to reduce final moisture content variability in kiln dried lumber by complementing conventional drying with radio frequency vacuum (RFV) drying technology. The strategy′s objective is to avoid producing over-dried lumber in conventional drying by setting the target moisture content to a value much higher than those usually used in industry. Then, RFV drying technology is implemented to quickly and efficiently re-dry the lumber that remains wet (under-dried) after the first conventional pass. Six experimental tests were performed in an industrial sawmill with the intention of studying the effect of target moisture content on the properties and quality of the dried lumber. In all cases, the first drying pass was performed in a 260m³ industrial heat-and-vent conventional kiln, and the re-drying of wets was performed in a 75m³ RFV kiln. Additionally, a mathematical model developed for prediction of data dispersion in lumber drying was calibrated with experimental data, and used to simulate the DSRD strategy under other hypothetical conditions. The results of the study demonstrate that the DSRD strategy reduces drying time, shrinkage and kiln drying degrade in comparison with a single conventional pass